2020
DOI: 10.33774/apsa-2020-4c0f2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“What’d We Miss?”: An Initial Analysis of Politics, Demographics, and COVID-19 Rates in Colleges’ Resumption of Instructional Operations for Fall 2020

Abstract: Generally, institutions who decided on an instructional mode of operation by June 15th remained steadfast in the decision on August 5th.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 1 publication
1
13
0
Order By: Relevance
“…This result may also be related to our finding that, among public institutions, location in a state with a GOP governor significantly and positively predicted the likelihood that it would shift to offering additional in-person instruction. This result confirms the findings of other recent work that explores institutional reopening plans (Andersen et al, 2020;Collier et al, 2020Collier et al, , 2021Felson & Adamczyk, 2021) and suggests that institutional leaders in some states were under considerable political pressure to reopen for in-person instruction, despite the health risks involved (Collier et al, 2020(Collier et al, , 2021Felson & Adamczyk, 2021). Indeed, our models indicate that political factors weighed more heavily than public health itself at the average public 4-year institution.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result may also be related to our finding that, among public institutions, location in a state with a GOP governor significantly and positively predicted the likelihood that it would shift to offering additional in-person instruction. This result confirms the findings of other recent work that explores institutional reopening plans (Andersen et al, 2020;Collier et al, 2020Collier et al, , 2021Felson & Adamczyk, 2021) and suggests that institutional leaders in some states were under considerable political pressure to reopen for in-person instruction, despite the health risks involved (Collier et al, 2020(Collier et al, , 2021Felson & Adamczyk, 2021). Indeed, our models indicate that political factors weighed more heavily than public health itself at the average public 4-year institution.…”
Section: Discussionsupporting
confidence: 90%
“…Subsequent research has confirmed that politics, especially party affiliation, played an important role in institutional decision-making. Studies from Collier et al, (2020Collier et al, ( , 2021 and Felson and Adamczyk (2021) indicate that states with either a Republican governor or a Republican-controlled legislature were more prone to reopen for in-person instruction.…”
mentioning
confidence: 99%
“…From the onset of the COVID-19 pandemic, there were sharp differences between Democrats and Republicans around reopening educational institutions and the economy (Parker et al, 2020). Research showed that universities, public and private, 2-and 4-year institutions, were affected by this political climate and there was significant association between reopening schools and a Republican governor (Collier et al, 2020(Collier et al, , 2021. The influence was most evident for 4-year public institutions that were more dependent upon public funding for their operations (Collier et al, 2021).…”
Section: The Covid-19 Pandemicmentioning
confidence: 99%
“…Yet, many argue that the education sector has been hit particularly hard because of the shift to wide-scale remote learning (Collier et al, 2021). In addition, at the postsecondary education level, the disparate ways institutions have chosen to respond to the pandemic has led to an array of approaches that all have nuanced impacts on students that we are only beginning to understand (e.g., Collier et al, 2020;Marsicano et al, 2020;Whatley and Castiello-Gutiérrez, 2021); further, higher education budgets are often the first victims of tightening state budgets. Importantly, researchers are making initial cases that remote learning during the pandemic has an exaggerated negative effect on STEM instruction and STEM students' performance (McCormick, 2021).…”
Section: Imbalance In the Ecosystem: Disrupting Progress In Stem Educationmentioning
confidence: 99%